Ciało w duchowości Ignacego Loyoli - Mateo Garcia Rogelio (Jesuit University Ignatianum in Krakow, 2017)
After his conversion, Ignatius of Loyola displayed Manichaeic hostility towards issues connected with the body. It led him to severe penance and rash fasting. Fortunately, he realized that this kind of reluctance towards the body is not the essence of following Christ. Grace does not destroy the nature, but it establishes and improves one. The body, though from the earth's dust, was formed by God. It serves man in order for him to express himself and act in the world creating his own history in a free and responsible way. However, after the original sin, the image of God - initially expressed in the body - was distorted. It was the incarnation of the Son of God and the work of salvation done by Him that led to the radical healing of this reality. Ignatian Spiritual Exercises constitute an example of enhancing the status of the bodily element in the spiritual life. It is to be apostolic, pervaded with the dynamism of the idea: "everything for the greater glory of God". "Everything" encompasses the whole world visible and invisible, the body and the soul, spiritual and material reality. Nothing should be excluded form the process of bringing glory to God and serving the man.